The Role of Excellence Service in Creating Customer Loyality (Case Study D'warung Sepakat Nikmat Kuta Bali) - Ramlatul Munawara; Alvan Fathony (Jurnal Mantik, 2021)
The purpose of this study is to explain how important the quality of a service is, especially Service Excellence, on customer satisfaction is mediated by customer satisfaction because the more rapid population growth, the more special needs such as food. Therefore, one of the fundamental factors is the existence of a Restaurant to support the need for food that serves a variety of interesting and distinctive menus. In today's competition in the business world, companies must prioritize customer satisfaction, which is one of the secrets to business success in a company. This research method uses qualitative research methods. The type of data used is the collection of various kinds of information and analysis. The concept of Excellence Service is a service that has quality services including speed, accuracy, reliability and empathy. The concept of Customer Loyalty as a need for customer loyalty (Customer Loyalty) which is related and has a close relationship with customer satisfaction. Excellence Services as the creator of Customer Loyalty at D' warung Sepakat Nikmat includes physical evidence, reliability, responsiveness, assurance, and empathy. External factors and internal factors that support the creation of customer loyalty and external factors that can hinder creating customer loyalty.